Physical activity counseling to cancer patients: How are patients addressed and who benefits most?. Issue 12 (December 2021) - Haussmann, Alexander; Ungar, Nadine; Tsiouris, Angeliki; Depenbusch, Johanna; Sieverding, Monika; Wiskemann, Joachim; Steindorf, Karen
Highlights: Most cancer patients report basic instead of an in-depth PA counseling. Only in-depth PA counseling is associated with PA levels of cancer patients. Patients with metastases are more responsive to in-depth PA counseling than survivors without metastases. Matched physician-patient data showed low agreements between these groups in PA counseling. Abstract: Objective: This study examined cancer patients' reporting on physicians' physical activity (PA) counseling, its associations with patients' PA, and comparisons of patients' and physicians' reports of the type(s) of PA counseling provided. Methods: Patients with breast, colorectal, or prostate cancer (n = 1206) participated in a nationwide cross-sectional study. Cancer patients' sociodemographic and treatment-related characteristics as well as self-reported PA levels (pre- and post-diagnosis) were assessed. PA counseling was queried according to the counseling steps of the 5As framework (Assess/Advise/Agree/Assist/Arrange). For a subsample (n = 135), matched patient-physician data were available. Results: Patient-reported PA counseling was categorized into "no counseling" (indicated by 20.8% of participants), "basic counseling" (Assess and/or Advise; 58.8%), and "in-depth counseling" (Agree, Assist, and/or Arrange; 20.4%). "In-depth counseling" was associated with an increase in PA levels pre- to post-diagnosis. This relationship was enhanced for patients with metastases. There were low agreements between patients' and physicians' reporting of PA counseling steps. Conclusion: In-depth PA counseling is rarely provided to cancer patients but seems to be required to affect PA levels. Patients often report receiving less intensive PA counseling than reported by their physician. Practice implications: Physicians should be enabled to provide routine in-depth PA counseling to all patients with cancer.